Erratum: Penerapan Metode Progresif Terhadap Hasil Belajar Keterampilan Handspring di Alat Meja Lompat - Fegie Rizkia Mulyana; Ridwan Gumilar (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.684 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.